ABOUT A METHOD OF EVALUATING STUDENTS’ KNOWLEDGE IN THEORETICAL MECHANICS LECTURES - Mahmudov Zakirjon Sotivoldievich; Rakhimov Abdulvoris Mutalovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
One of the main tasks of today is to use modern evaluation systems along with traditional methods in assessing the level of students’ knowledge. It is shown that the method of the confused logical chain, which is proposed to be used to increase the activity of students in the training of theoretical mechanics taught in higher educational institutions, can be applied to science.